2018
DOI: 10.1186/s41824-017-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

18F- FDG PET/CT joint assessment of early therapeutic response in rheumatoid arthritis patients treated with rituximab

Abstract: Background18F–FDG PET/CT has been proposed in the evaluation of the disease activity in rheumatoid arthritis (RA). The goals of this study were to evaluate the reproducibility of the technique, to compare metabolic parameters to clinical, biological and ultrasonographic parameters before and after treatment and to evaluate whether the early metabolic response was related to the outcome. 18F- FDG PET/CT of the hands, wrists and knees was obtained in 15 patients with anti-TNFα refractory RA, at baseline and 16 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…The 18 F-FDG sensitivity found in our study of 34% was lower. While the mean DAS28 score of 5.4 is representative for an RA patient population with moderate-to-high disease activity, the median CRP value found in our study was relatively low (3.0 (range: 1.5–24.5) mg/L) when compared to values found in the literature [6, 7, 48, 49]. It is possible that the low CRP levels in our study reflect a population with milder systemic inflammatory activity, which could in part explain the overall lower level of 18 F-FDG sensitivity.…”
Section: Discussioncontrasting
confidence: 80%
“…The 18 F-FDG sensitivity found in our study of 34% was lower. While the mean DAS28 score of 5.4 is representative for an RA patient population with moderate-to-high disease activity, the median CRP value found in our study was relatively low (3.0 (range: 1.5–24.5) mg/L) when compared to values found in the literature [6, 7, 48, 49]. It is possible that the low CRP levels in our study reflect a population with milder systemic inflammatory activity, which could in part explain the overall lower level of 18 F-FDG sensitivity.…”
Section: Discussioncontrasting
confidence: 80%
“…While not well-studied in the facet joints, there is evidence that FDG activity can indicate an early response to systemic treatment in other inflammatory conditions, including inflammatory arthritis. 17,18 We found that high-grade perifacet findings were more common with gadolinium, supporting the assertion that further investigation with MR imaging protocols including gadolinium, rather than fat-suppressed T2 images alone, would be reasonable. The results also provide initial assessment of the approximate frequency and concordance of potential imaging biomarkers on multiplane fat-suppressed T2, fat-suppressed T1 gadolinium-enhanced, and FDG-PET images using a standardized protocol.…”
Section: Discussionsupporting
confidence: 66%
“…► Joint and vascular inflammations as determined by PET/CT exerted multiple correlations with autoantibodies, systemic inflammation, lipids, carotid atherosclerosis and arterial stiffness. RMD Open RMD Open RMD Open predict clinical outcome in patients with RA undergoing combination conventional synthetic disease-modifying antirheumatic drug (csDMARD), 30 anti-tumour necrosis factor, 17 31-33 rituximab 34 or tocilizumab therapy. 35 In AS, the effects of statins could be monitored by PET/CT.…”
Section: What Does This Study Add?mentioning
confidence: 99%